LAW ENFORCEMENT AGAINST PLACEMENT OF INDONESIAN MIGRANT WORKERS IN RIAU PROVINCE BASED ON LAW NUMBER 18 OF 2017 ON PROTECTION OF INDONESIAN MIGRANT WORKERS - Maesyarifah, Agesti Absah; Fahmi, Sudi; Ardiansah, Ardiansah (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2025)
ABSTRACT Pasal 81 Undang–Undang Nomor 18 Tahun 2017 tentang Perlindungan Pekerja Migran Indonesia, mengatur sanksi hukum bagi orang perseorangan yang melaksanakan penempatan Pekerja Migran Indonesia dengan pidana maksimal 10 tahun dan denda maksimal Rp. 15.000.000.000,00. Metode penelitiaan ialah penelitian hukum sosiologis dengan pendekatan perundang–undangan, kasus dan analitis lokasi penelitian: Kepolisian Daerah Riau; populasi dan sampel dari narasumber relevan; sumber data: primer, sekunder dan tersier; teknik pengumpulan data: observasi, wawancara terstruktur dan studi dokumen/kepustakaan; analisis data: kualitatif dengan kesimpulan induktif. Hasil penelitian adalah penegakan hukum yang dimaksudkan belum terlaksana dengan baik Kesimpulannya adalah Penegakan hukum terhadap pelaku penempatan Pekerja Migran Indonesia di Provinsi Riau berdasarkan regulasi tersebut belum terlaksana dengan baik tahun 2021 sampai 2023 karena beberapa pelaku belum tertangkap. faktor penghambatnya ialah faktor aparat penegak hukum/ pmerintah, faktor sarana/ fasilitas dan faktor masyarakat.Kata Kunci: TPPO, Pekerja Migran Indonesia, Riau ABSTRAK Article 81 of Law Number 18 of 2017 on the Protection of Indonesian Migrant Workers regulates legal sanctions for individuals who engage in the placement of Indonesian Migrant Workers, with a maximum penalty of 10 years imprisonment and a fine of up to IDR 15,000,000,000. The research method employed is sociological legal research using statutory, case-based, and analytical approaches. The research location was the Riau Regional Police; the population and sample consisted of relevant resource persons. Data sources included primary, secondary, and tertiary data. Data collection techniques included observation, structured interviews, and document/library studies. Data analysis was conducted qualitatively, with conclusions drawn inductively. The research findings reveal that law enforcement as intended has not been effectively implemented. The conclusion is that law enforcement against individuals involved in the placement of Indonesian Migrant Workers in Riau Province based on the stated regulations has not been adequately carried out from 2021 to 2023, as several offenders have yet to be apprehended. The inhibiting factors include law enforcement/government personnel, inadequate infrastructure/facilities, and societal factors. Kata Kunci: TIP, Indonesian Migrant Workers, Riau